The Determination of Contracts in Agricultural Economies - Leonardo Lanzona (Philippine Institute for Development Studies (PIDS), 2007)
This paper aims to analyze how contracts are determined and modified given diverse agricultural settings and to examine the implications of these changes with respect to their efficiency, distribution, and sustainability. The contract model presented here differs from previous contract models as the enforcement issues regarding contracts across various agro-climatic and output conditions are considered. Emphasis is placed on the effects of the shifts in production resulting from historical changes in both policy and production environments on the development contracts. Moreover, the consequences of the enforcement costs of contractual arrangements will be examined. Although much of the focus is on the rice economy, this paper attempts to provide an integrative description of the various agricultural contracts in different places in the Philippines. This will integrate the papers written on the contracts found in the fishing industry, the contract growing arrangements in Mindanao, and the contracts in swine, vegetable, and mango production. Along with secondary data, the methodology for gathering data for this research includes rapid appraisal surveys and field interviews.
Keywords: 330; agricultural contracts; contract growing; contract model; agriculture production; Agrarproduktion; Transaktionskosten; Prinzipal-Agent-Theorie; Theorie; Landwirtschaft; Philippinen